Teacher Strategies for Social-Emotional Development in Early Childhood at Nathawee Municipal School, Thailand - Pratiwi, Iswanda Riski; Lasarus, Yes Matheos; Maulidiyah, Eka Cahya; Widayanti, Melia Dwi (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2025)
This study aims to describe teacher strategies in implementing learning that supports the social-emotional development of early childhood at Nathawee Municipal School, Thailand. The study used a qualitative descriptive method with data collection techniques including observation, in-depth interviews, and documentation. The findings indicate that teachers applied strategies rooted in local culture and consistent daily routines, such as Thai-style greetings, flag ceremonies, morning milk queues, and independence routines like brushing teeth, bathing, and bed-making. Additional strategies include storytelling with Thai folktales, emotional discussions, and collaborative group work. These approaches proved effective in fostering empathy, independence, and emotional regulation in young children.